1981
DOI: 10.1128/jcm.13.6.1017-1022.1981
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of pharyngeal carriers of beta-hemolytic streptococci among school children in Sapporo City during a period of 2 years and 5 months

Abstract: A total of 124 normal school children in three classes (aged 8 to 9) were examined for beta-hemolytic streptococci for 29 months from August 1977 to December 1979 by means of serial monthly throat cultures. No significant difference between the carrier rate of boys and that of girls was observed. Although no monthly variation of carrier rates appeared in class II, marked temporal increases of carrier rates appeared from June 1978 (in Class I) and from August 1978 (in class III) to August 1979. These periodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…This is in contrast to several reports from the USA [1,2,36]. On the other hand, our data and those of Maekawa and co-workers [37] from Japan and Hoffman [38] from Denmark showed that females and males are equally susceptible to throat streptococcal infection. In contrast APSGN was more frequent among boys than girls (1P9:1), which is in line with earlier reports [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to several reports from the USA [1,2,36]. On the other hand, our data and those of Maekawa and co-workers [37] from Japan and Hoffman [38] from Denmark showed that females and males are equally susceptible to throat streptococcal infection. In contrast APSGN was more frequent among boys than girls (1P9:1), which is in line with earlier reports [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Reports on the seasonal variation in the incidence of beta-haemolytic streptococci in a population are inconsistent. In the temperate regions the general observation is that the carrier rate of GAS is high during the winter season [24], while others have failed to demonstrate such periodicity [37,51]. In a 3-year study of Egypt, a sharp rise in the isolation rate of GAS from schoolchildren was noted during late autumn and early winter with a minimum rate in the summer months [8].…”
Section: Discussionmentioning
confidence: 99%
“…This rules out the possibility that the predominance of pharyngitis caused by emm6 and emm1 isolates was due to a background GAS population composed of rare or "less virulent" serotypes that had a low probability of causing disease. Other studies have reported an increase in the prevalence of specific GAS emm types (including emm6 and emm1) in noninvasive disease or asymptomatic carriage in civilian and military populations [18,22,25,36,37]. For example, emm6 isolates caused an increase in cases of pharyngitis during the course of a surveillance study of a semiclosed population in Red Lake, Minnesota [38].…”
Section: Discussionmentioning
confidence: 97%
“…injection with formalin-killed bacteria. The procedures for preparation of formalin-killed bacteria, immunization of rabbits and preparation of monospecific typing sera by absorption of the antisera with cross-agglutinating strains followed essentially those prescribed for T-typing agglutination of Streptococcus pyogenes (7,11).…”
Section: Methodsmentioning
confidence: 99%